Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Mie Gacoan Cabang Marapalam - Ziqra Ahmad Fauzi; Siska Lusia Putri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the Effect of Product Quality and Service Quality on Purchasing Decisions at Mie Gacoan, Marapalam branch in Padang City (Case study of undergraduate students of Management at Unidha)". The population in this study were 414 undergraduate students of Management at Dharma Andalas University, Padang, with a sample size of 104 respondents. Data were obtained by distributing questionnaires, then processed and tested using IBM SPSS Statistics 22. From the research conducted, it is known that based on the results of hypothesis testing, 1). Product Quality has a positive and significant effect on Purchasing Decisions, 2). Service Quality has a positive and significant effect on Purchasing Decisions, 3). Product Quality and Service Quality have a positive and significant effect on Purchasing Decisions. Furthermore, the Purchasing Decision variable is influenced by Product Quality and Service Quality by 61.1%, which is classified as moderate, the remaining 38.9% is influenced by other variables not included in this study, namely Marketing Strategy, Lifestyle, and Purchase Interest.